MANAJEMEN NONFARMAKOTERAPI BAGI PASIEN PPOK (Nonpharmacotherapy management for patient with COPD) - Lilyana, Maria Theresia Arie Lilyana (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2017)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by productive cough, dyspnea and chronic airway obstruction. Management of COPD is to reduce symptoms, and the way to achieve it with pharmacology and non-pharmacology therapy such as quitting smoking, pulmonary rehabilitation and prevent malnutrition. Method: This is a literature review of nonpharmacotherapy management for COPD. Result: Therapy that we can give to patients with COPD are to stop smoking, because smoking can disrupt pulmonary function. Pulmonary rehabilitation aimed at reducing breathing difficulties in cases of COPD. Adequate nutritional for COPD patients is expected to increase muscle weight and strength and quality of life for patients with COPD who are malnutrition. Recommendations: Non-pharmacotherapy management that can be given to COPD patients include recommendations for smoking cessation, pulmonary rehabilitation and prevent malnutrition.